Churchill an illustrated life - Lewis, Brenda Ralph (Amber Books, 2019)
"This book is a celebration of the life of one of Britain's greatest statesmen. Churchill's career has few parallels in British history for richness, range, length and achievement. He was an early pioneer of Britain's welfare state and played a key role in preparing the Royal Navy for World War I. In World War II he emerged as an inspiring, charismatic leader and was a prime architect of the final victory in Britain and the United States. Illustrated with magnificent photographs, and featuring extracts from his most brilliant speeches, this book covers the whole life of this most colourful of men."